IMPLEMENTATION OF PROGRAMMABLE LOGIC CONTROLLER IN AN AUTOMATIC MANDAC CRAB SORTING SYSTEM BY WEIGHT: IMPLEMENTATION OF PROGRAMMABLE LOGIC CONTROLLER IN AN AUTOMATIC MANDAC CRAB SORTING SYSTEM BY WEIGHT - Handika Nadyawan, Ahmad; Rahmawat, Diana; Sukri, Hanifudin (UPMI Proceeding Series, 2023)
In the early 1980s, one of the fishery commodities, namely mud crabs, became an important commodity in Indonesia. The majority of the economic potential came from the wealth of the sea, specifically the increased production of mud crabs, especially in Ujungpangkah Village, Gresik Regency. This increase was influenced by the high demand for various types of mud crabs every day. The fundamental problem in the harvesting process of mud crabs still relied on conventional methods, which involved weighing and sorting each crab based on its weight. This method required a significant amount of manpower and time to complete the process, resulting in delays in distribution and marketing, which significantly affected the harvest yield and customer trust.This research aims to design an automation system that suits the field conditions, specifically an automatic sorting system for mud crabs controlled by a Programmable Logic Controller (PLC) Omron CP1E-N30DT-A and Arduino NANO, which communicate with each other to provide logical instructions. The system also employs a PID (Proportional Integral Derivative) controller to control the DC (Direct Current) motor of the conveyor. The sorting device created is a conveyor that transports the crabs to an automatic load cell sensor for weight reading.